2009
DOI: 10.1152/japplphysiol.91505.2008
|View full text |Cite
|
Sign up to set email alerts
|

A novel hindlimb immobilization procedure for studying skeletal muscle atrophy and recovery in mouse

Abstract: Skeletal muscle atrophy is a serious concern for patients afflicted by limb restriction due to surgery (e.g., arthrodesis), several articular pathologies (e.g., arthralgia), or simply following cast immobilization. To study the molecular events involved in this immobilization-induced debilitating condition, a convenient mouse model for atrophy is lacking. Here we provide a new immobilization procedure exploiting the normal flexion of the mouse hindlimb using a surgical staple to fix the ventral part of the foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
108
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(123 citation statements)
references
References 57 publications
12
108
1
2
Order By: Relevance
“…For example, eukaryotic initiation factor (eIF)-3f, a protein that is critical for the commencement of translation initiation, is degraded by the ubiquitin E3 ligase MAFbx/ atrogin-1 (4,5). It has been shown that the prevention of polyubiquitination of eIF3f reduces starvation-induced muscle atrophy (9,10). Moreover, myostatin-induced myotube atrophy is associated with the upregulation of components of the ubiquitin-proteasome pathway but also degradation of proteins associated with ribosomal biogenesis, translation initiation, and elongation as well as a reduction in MPS (11,12).…”
Section: Regulation Of Protein Metabolism In Human Disuse Atrophy: Nomentioning
confidence: 99%
See 1 more Smart Citation
“…For example, eukaryotic initiation factor (eIF)-3f, a protein that is critical for the commencement of translation initiation, is degraded by the ubiquitin E3 ligase MAFbx/ atrogin-1 (4,5). It has been shown that the prevention of polyubiquitination of eIF3f reduces starvation-induced muscle atrophy (9,10). Moreover, myostatin-induced myotube atrophy is associated with the upregulation of components of the ubiquitin-proteasome pathway but also degradation of proteins associated with ribosomal biogenesis, translation initiation, and elongation as well as a reduction in MPS (11,12).…”
Section: Regulation Of Protein Metabolism In Human Disuse Atrophy: Nomentioning
confidence: 99%
“…To illustrate the gaps in our mechanistic understanding of this condition, let us briefly consider what is currently known about a well-established and reliable mouse model of immobilization-induced muscle atrophy. In this model, one tibialis anterior muscle in each mouse is immobilized with a metal clip, which, similar to a cast, induces progressive muscle atrophy that is localized to the immobilized muscle (10). Skeletal muscle atrophy in this model, like other forms of skeletal muscle atrophy in humans or mice, is highly complex at the molecular level.…”
Section: Insights Into Disuse Muscle Atrophy Using Systems Approachesmentioning
confidence: 99%
“…To induce damage, 40 mL of 10 mM cardiotoxin (CTX; Latoxan, Valence, France) was injected into the TA muscles, as described previously. (18,21,28) Contralateral TA muscles injected with 40 mL of 0.9% saline solution were used as controls. Alternatively, the TA muscles were damaged by crushing with surgical tweezers.…”
Section: Animalsmentioning
confidence: 99%
“…In humans, a reduction in myostatin expression associated with muscle hypertrophy has been observed 39 . Caron et al 40 identified that skeletal muscle atrophy could be associated with the up-regulation of myostatin. Interestingly, the gene expression of NFκB at 2 days in the inflammation group was also unexpectedly reduced in our study.…”
Section: Muscle Response To Joint Inflammationmentioning
confidence: 99%
“…This response confirms the pivotal role of the ubiquitin-proteasome pathway and of protein degradation in the early stage of atrophy in muscles that have been subjected to immobilization 13,14,16 . The up-regulation of those genes could be influenced by the elevated oxidative stress following immobilization 40,42 . The upregulation of MyoD at 2 days in the immobilization group could be related to a possible change from type I to type II fibers, as reported during the atrophic process in slow-twitch muscles 25,43 .…”
Section: Muscle Response To Immobilizationmentioning
confidence: 99%